Risk Differences between Elderly Men and Women toward Doctor-Diagnosed Diabetes Mellitus in Urban Areas in Indonesia: 2013 National Basic Health Research Data - Budiharsana, Meiwita (UI Scholars Hub, 2017)
Diabetes melitus (DM) adalah salah satu penyakit tidak menular yang paling umum di Indonesia. DM disebabkan berbagai faktor risiko. Peningkatan prevalensi DM salah satunya disebabkan oleh perubahan gaya hidup di perkotaan. Penelitian ini bertujuan untuk menguji perbedaan prevalensi DM yang didiagnosis dokter pada laki-laki dan perempuan usia 15 tahun keatas yang tinggal di daerah perkotaan di Indonesia. Analisis menggunakan data sekunder Riset Kesehatan Dasar (Riskesdas) 2013 dengan desain studi potong lintang. Total sampel sebanyak 333.731 responden. Metode analisis menggunakan regresi logistik ganda. Hasil menunjukkan bahwa DM yang didiagnosis dokter pada laki-laki dan perempuan usia 15-39 tahun di perkotaan tidak berbeda. Meski demikan, memasuki kurun usia 50-64 tahun, responden perempuan menunjukkan risiko terdiagnosis DM 30 kali lebih tinggi dibandingkan perempuan berusia 15-39 tahun, sementara laki-laki berusia 50-64 tahun berisiko 21 kali lebih tinggi dari laki-laki berusia 15-39 tahun (nilai p < 0,001). Penelitian ini menyimpulkan perempuan dan laki-laki berusia lanjut jauh lebih berisiko didiagnosa DM dibandingkan berusia lebih muda. Diabetes mellitus (DM) is one of the most common non-communicable diseases (NCDs) in Indonesia. Reportedly that DM is associated with various risk factors. Notably, it seems that the rising prevalence rates reflect changes in urban lifestyle. This study aimed to examine risk differences in the prevalence of DM among men and women aged 15 years and older that lived in urban areas in Indonesia. Analysis used secondary data of 2013 National Basic Health Research, which applied a cross-sectional study design. The total of sample was 333,731 respondents. Data processing and analysis used multiple logistic regression method. In general, findings showed that doctor-diagnosed diabetes mellitus (DDDM) among urban men and women aged 15-39 years did not differ. However, the odds ratio of DDDM among older women aged 50-64 years was 30 times higher than women aged 15-39 years, while among the same age men was 21 times higher than younger men aged 15-39 years (p value < 0.001). In conclusion, entering the age of 50 years, women show a much higher risk of contracting DDDM than women with younger age, also much higher than older men towards younger men.